ATP- and Adenosine-Mediated Signaling in the Central Nervous System: Purinergic Receptor Complex: Generating Adenine Nucleotide-Sensitive Adenosine Receptors - Kazuaki Yoshioka; Hiroyasu Nakata (Journal of Pharmacological Sciences, 2004)
Adenosine A1 receptors (A1R) are able to form a heteromeric complex with P2Y1 receptors (P2Y1R) that generates A1R with P2Y1R-like agonistic pharmacology. A potent P2Y1R agonist, adenosine 5′-O-(2-thiotriphosphate), binds the A1R binding pocket of the A1R/P2Y1R complex and inhibits adenylyl cyclase activity via Gi/o protein. These mechanisms might be used to fine-tune purinergic inhibition locally at sites where there is a particular oligomerization structure between purinergic receptors and explain the undefined purinergic functions by adenosine and adenine nucleotides. Keywords:: oligomerization, purinergic receptor, bioluminescence resonance energy transfer system (BRET), immunoprecipitation, G protein-coupled receptor